MENIMBANG MAKNA ULIL AMRI: KEPEMIMPINAN DALAM TAFSIR NUR AL-IḤSAN TERHADAP QS. AN-NISA’ AYAT 59 - Mayasari Mayasari (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This article discusses leadership in Islam as an issue that must be deeply examined for the continuity of the Muslim community. One of the contexts explored is leadership in the Malay world under foreign colonial rule. This is evidenced by the emergence of the Tafsir Nūr al-Iḥsān, which addresses verses concerning leadership. The purpose of this study is to examine the context of leadership during the time of Muhammad Sa‘id as reflected in his tafsir, focusing specifically on Surah an-Nisā’ verse 59. This research employs a qualitative method, using library research with both primary and secondary sources. The primary source is the Tafsir Nūr al-Iḥsān, while secondary data are drawn from books and journals. The data are analyzed through content analysis by examining the historical context using Hans-Georg Gadamer’s hermeneutical theory.The results of the study reveal that Tuan Haji Muhammad Sa‘id bin ‘Umar’s interpretation of Surah an-Nisā’ verse 59 in Tafsir Nūr al-Iḥsān provides a highly relevant perspective within the socio-political context of Kedah during the colonial period. The verse emphasizes the importance of obedience to Allah, the Prophet, and legitimate leaders. For Sa‘id ‘Umar, a true leader is one who upholds the laws of Allah and strives to embody divine justice. Historically, the Sultan of Kedah continued to play a central role as a symbol of Islamic leadership, although British colonial influence at the time dominated governance. Sa‘id ‘Umar asserted that obedience to leaders is only valid as long as those leaders prioritize the principles of Islamic law.